Legal Protection and Principles of Justice for Women Post-Annulment of Marriage in Asset Division - Moh Ainul Yakin; Ali Ma’ruf; Ervita Septyanto Putri; Haidi Muslim; Michael Gilrandy Kurniawan (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2024)
The conception of marriage law in Indonesia is categorised into three groups, the first being the concept based on the Burgelijk Wetboek, the second after the enactment of the Marriage Law, and the third in accordance with Islamic law. A valid marriage gives rise to rights and obligations for both spouses, as well as property and children born during the marriage. However, if the marriage that is carried out does not meet the legal requirements of marriage, implications may arise, as illustrated in a case in South Kalimantan where the ex-wife tried to annul her husband's marriage to another woman. On these issues, this study examines the legal protection and application of the principles of justice for women in the context of the division of common property after the annulment of marriage. The main focus of the research is to analyze the legal impact of marriage annulment on women's rights to joint property and identify gaps in existing regulations. The research method used is normative juridical with a statutory and conceptual approach. The results show that women are often in a vulnerable position after marriage annulment, especially in terms of the division of joint property. Although the Marriage Law and the Compilation of Islamic Law regulate the division of joint property, its implementation in cases of marriage annulment still creates legal uncertainty. The principle of justice has not been fully realized.